An analysis of types of taboo words among teenagers in the It (2017) movie - Dhea Ayu Styowati; Rosita Ambarwati; Kristiasih Kristiasih (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
This research aims to find the types of taboo words uttered by teenage teenage characters in It (2017) movie. This research used a descriptive qualitative method. The source of the data were the video of It (2017) movie and the transcript. The data of this research are words, phrases, clauses, and sentences uttered by teenage teenage characters of It (2017) movie. The data were collected by watching the video repeatedly and then matching the transcript and the video carefully. Then the raw data were analyzed by applying Jay (1992) theory. Based on the data analysis, it was found seven types of taboo words uttered by teenage teenage characters in It (2017) movie. The most frequently used is epithet which appear 84 times (52%), followed by insult and slur which appear 39 times (24%), obscenety which appear 17 times (10%), vulgarity which appear 7 times (4%), profanity which appear 6 times (4%), and scatology and cursing which appear 5 times each (3%).